Taking agricultural technologies to scale: experiences from a vegetable technology dissemination initiative in Tanzania - Gramzow, Andreas; Sseguya, H.; Afari-Sefa, Victor; Bekunda, Mateete A.; Lukumay, Philipo J. (Informa UK Limited, 2018)
One of the widely suggested approaches to meet the increasing food demand of a substantially growing world population is sustainable intensification. We present a unique agricultural research and scaling programme in Tanzania, focusing on the key elements necessary for results related to: gender analysis; private sector engagement; social capital; improvement and adaptation; and programme performance monitoring and evaluation. Since 2014, more than 6000 farmers have benefited from either the adaptive research or the scaling component of the programme. Preliminary impact analysis results from six pilot locations indicate that programme participants realized significantly higher yields compared to non-participants. In addition to productivity improvements, introducing resistant and drought-tolerant elite vegetable varieties improved the resilience of the existing farming systems. Finally, considering the needs of both male and female participants had a positive impact on technology adoption rates and reach.